2008
DOI: 10.2134/jeq2007.0268
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen, Tillage, and Crop Rotation Effects on Nitrous Oxide Emissions from Irrigated Cropping Systems

Abstract: We evaluated the effects of irrigated crop management practices on nitrous oxide (N(2)O) emissions from soil. Emissions were monitored from several irrigated cropping systems receiving N fertilizer rates ranging from 0 to 246 kg N ha(-1) during the 2005 and 2006 growing seasons. Cropping systems included conventional-till (CT) continuous corn (Zea mays L.), no-till (NT) continuous corn, NT corn-dry bean (Phaseolus vulgaris L.) (NT-CDb), and NT corn-barley (Hordeum distichon L.) (NT-CB). In 2005, half the N was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(107 citation statements)
references
References 22 publications
9
95
1
2
Order By: Relevance
“…On the other hand, there is growing evidence that enhancedefficiency fertilizers such as slow and controlled release and stabilized N fertilizers can enhance crop recovery of fertilizer N and minimize nutrient losses to the environment (Snyder et al 2007). Their potential to reduce N 2 O emissions is however, unclear; few investigations have documented abatement (Halvorson et al 2008). …”
Section: Fertilizer N Typementioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, there is growing evidence that enhancedefficiency fertilizers such as slow and controlled release and stabilized N fertilizers can enhance crop recovery of fertilizer N and minimize nutrient losses to the environment (Snyder et al 2007). Their potential to reduce N 2 O emissions is however, unclear; few investigations have documented abatement (Halvorson et al 2008). …”
Section: Fertilizer N Typementioning
confidence: 99%
“…Numerous field studies conducted on N input gradients in row-crop agriculture have found that emissions of N 2 O correlate well with fertilizer N rate (e.g., MacKenzie et al 1998;Bouwman et al 2002a;McSwiney and Robertson 2005;Mosier et al 2006;Drury et al 2008;Dusenbury et al 2008;Halvorson et al 2008;Hoben et al 2010, in review;Millar et al 2010, in review). In all of these studies, increasing the amount of N added to soil resulted in increasing emissions of N 2 O.…”
Section: Fertilizer N Ratementioning
confidence: 99%
See 1 more Smart Citation
“…As reviewed by Mosier et al (1998) and Kroeze et al (1999), agriculture activities contributed about 78% of global anthropogenic N 2 O emission, 67% of which is from agricultural soil. Therefore, a great number of studies have been conducted on N 2 O flux measurements over agricultural fields (e.g., Sehy et al, 2003;Venterea et al, 2005;Stehfest and Bouwman, 2006;Phillips, 2007;Halvorson et al, 2008;Ussiri et al, 2009;Zaman and Nguyen, 2010). These measurements greatly extended the database * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…In years with above average rainfall Wiedenfeld (1986) found that cabbage (Brassica oleracea L. Group capitata) and onion (Allium cepa L.) had increased yield, yield weight and leaf N content when grown with slow-release fertilizers, methylene urea and sulfur-coated urea, but there were no differences when rainfall was below average. Halvorson et al (2008) studied N 2 O gas flux emission from irrigated corn (Zea mays L.), wheat (Triticum aestivum L.), barley (Hordeum vulgare) and dry bean (Phaseolus vulgaris) treated with various N fertilizers on clay loam in the western great plains. Under irrigation, the polymer coated urea reduced N 2 O emissions from the four irrigated crops.…”
Section: Discussionmentioning
confidence: 99%